Evaluation-Based Curriculum Analysis: A Paradigm Shift in Assessment in the Merdeka Curriculum - Julhadi, Julhadi; Hidayati, Sri; Yakub, Ramli; Fadli, Rahmat; Kemerindo, Gref (Ahlussunnah: Journal of Islamic Education, 2025)
The curriculum in Indonesia continues to evolve in response to the country's conditions. The transition from the 2013 Curriculum (K13) to the Merdeka Curriculum (KM) marks a fundamental shift, particularly in the assessment paradigm. This study aims to analyze how the Merdeka Curriculum is designed based on evaluation, focusing on the philosophical shift and practical implementation of diagnostic, formative, and summative assessments. The research method used is descriptive qualitative with a library research approach. Primary and secondary data were analyzed from 17 references, including official guidelines from the Ministry of Education, Culture, Research, and Technology, textbooks, and scientific journal articles (2018-2025). The results of the analysis show that the Merdeka Curriculum replaces the rigid Minimum Completion Criteria (KKM) with more flexible Learning Objective Achievement Criteria (KKTP), which can be compiled using criteria descriptions, rubrics, or value intervals. The essence of this shift is the strengthening of formative assessment as assessment for learning and assessment as learning, which aims to continuously improve the learning process. Diagnostic assessment (cognitive and non-cognitive) is now required at the beginning to map students' needs. While summative assessments continue to be used as assessments of learning to measure final achievement, authentic assessments, such as performance assessments, projects, and portfolios, are strongly encouraged to measure 21st-century competencies in real-world contexts. The implication of these findings is that there is an urgent need for more practical teacher training to address misconceptions about implementation and improve assessment literacy.